2021
DOI: 10.1007/s00412-021-00760-1
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling HP1 functions: post-transcriptional regulation of stem cell fate

Abstract: Heterochromatin protein 1 (HP1) is a non-histone chromosomal protein first identified in Drosophila as a major component of constitutive heterochromatin, required for stable epigenetic gene silencing in many species including humans. Over the years, several studies have highlighted additional roles of HP1 in different cellular processes including telomere maintenance, DNA replication and repair, chromosome segregation and, surprisingly, positive regulation of gene expression. In this review, we briefly summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 113 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…To further investigate the hypothesis and examine the putative GSC cluster, we plotted the GSC-related gene expression in pseudotime. Similar expression profiles of functional GSC differentiation genes (bam, bgcn, out, twin and Set1) (43)(44)(45)(46) and GSC maintenance genes (aret, Mei-P26, egg, Myc and Hrb98DE) (47)(48)(49)(50)(51) were showed in trajectory (Fig. 2D).…”
Section: Identification Of Gsc Cluster and 2 Distinct Undifferentiate...mentioning
confidence: 54%
“…To further investigate the hypothesis and examine the putative GSC cluster, we plotted the GSC-related gene expression in pseudotime. Similar expression profiles of functional GSC differentiation genes (bam, bgcn, out, twin and Set1) (43)(44)(45)(46) and GSC maintenance genes (aret, Mei-P26, egg, Myc and Hrb98DE) (47)(48)(49)(50)(51) were showed in trajectory (Fig. 2D).…”
Section: Identification Of Gsc Cluster and 2 Distinct Undifferentiate...mentioning
confidence: 54%
“…Large-scale mapping of in vivo binding sites of chromatin proteins using tethered dam methyltransferase [96,97] showed that the clustered Bari1 elements in the h39 region of the 2nd chromosome are targets of HP1, a chromatin protein mainly involved in heterochromatin formation [98]. It has been reported that Bari1 also contains Polycomb responsive elements that could collaborate in recruiting additional heterochromatin components [91].…”
Section: Possible Role In Chromatin Assemblymentioning
confidence: 99%
“…To further investigate this hypothesis and examine the putative GSC cluster, we plotted the GSC‐related gene expression in pseudotime. Similar expression profiles of functional GSC differentiation genes ( bam , bgcn , out , twin , and Set1 ; Steinhauer & Kalfayan, 1992; Ohlstein et al , 2000; Fu et al , 2015; Vidaurre & Chen, 2021) and GSC maintenance genes ( aret , Mei‐P26 , egg , Myc , and Hrb98DE ; Rhiner et al , 2009; Ji & Tulin, 2012; Blatt et al , 2020; Rastegari et al , 2020; Casale et al , 2021) were revealed in the trajectory (Fig 2E). Consistent with our expectations, we observed low expression of genes associated with differentiation and high expression of genes associated with self‐renewal, while their expression patterns along the trajectory were gradually changed over time.…”
Section: Resultsmentioning
confidence: 99%